Diseño del hostal “PARADISE”, mediante la elaboración del plan de negocios, para fortalecer el turismo en la Parroquia Pacayacu, Cantón Lago Agrio, Provincia de Sucumbíos - Rea Barragán, Marlon Ramiro (2018)
The objective of the present investigation is to carry out the DESIGN OF THE HOSTAL "PARADISE", THROUGH THE DEVELOPMENT OF THE BUSINESS PLAN, TO STRENGTHEN THE TOURISM IN THE PACAYACU PARISH, CANTON LAGO AGRIO, PROVINCE OF SUCUMBIOS, which allowed the use of different methods and techniques that research allows to perform, such as the Deductive method, the Inductive Method, the Descriptive Method and the Analytical Method, as well as the use of bibliographic materials, surveys and virtual material. The use of all these methods and techniques made it possible to reach the culmination of this work, since in order to achieve it, it was necessary to follow the steps of application, understanding and demonstration of it. In the market study carried out in the Lago Agrio canton, with a sample of 310 people; tabulated the surveys have been analyzed and the results have been inferred to then perform the market analysis, determining the Potential Demand of 112.501, the Real Demand 110,251 PEA, Effective Demand of 307,600. The Unsatisfied Demand of 307,600 services, which allowed to determine that the project can and should be executed, by the results obtained in the analysis of the demand, the offer and marketing levels of this service. The installed capacity of the project determines that the company will be able to offer 4,380 services and its utilized capacity will be of 4,380 services, of which 1.42% of the unsatisfied demand will be used, and the location of the same will be determined. located in the city of Nueva Loja. The service process demands the use of adequate equipment, which will guarantee a quality service at moderate prices. Likewise, an administrative study was carried out determining as a Limited Liability Company, and with the functional organic structure at the hierarchical 5 levels both Legislative, Executive, Advisory Level, Support Level Support, Operational Level, as well as the function manuals, organizational charts; which served as a guideline to implement a good organization, since it will have the following staff: Manager, a Contadora Secretary, a Guardian, who will be part of the Administrative staff. The project reaches an investment of 105,073.17 dollars and will be financed with a contribution from the partners of 62% of the total investment that corresponds to 65,073.17 dollars and a loan that will maintain the project with the CFN will constitute the 38% that corresponds to 20,000.00 dollars at 5 years term at 11.5% annual interest. The financial evaluation presents the following results: according to the NPV of this project, it gives us a positive value of 44,747.07 dollars, which indicates that the project or investment is convenient. For the present project, the TIR is 12.62%, this value being satisfactory for carrying out the project, the time that would be required to recover the original investment would be 4 years, 7 months and 13 days, for the present project, the sensitivity values are less than one, therefore the changes in costs and revenues increased 14.39% and decreased by 9.09%, respectively, that is, the project is not sensitive to these changes